Neutrosophic MAGDM Based on CRITIC-EDAS Strategy Using Geometric Aggregation Operator - Mallick, Rama; Pramanik, Surapati; Giri, Bibhas Chandra (Yugoslav Journal of Operations Research; Vol 33 No 4 (2023), 2023)
Nowadays career choosing is a very difficult job for many students. This paper primarily addresses the concerns of those students who face difficulty in choos- ing the right career option for themselves, using multi-attribute group decision-making (MAGDM) methodologies based on CRITIC (Criteria Importance Through Inter criteria Correlation) and EDAS (Evaluation based on Distance from Average Solution) strate- gies under the single-valued neutrosophic set (SVNS) environment. First, the CRITIC strategy is used to calculate the weights of the attributes and then these weights are used to develop EDAS strategy in the SVNS environment. Since the usage of the geo- metric operator CRITIC-EDAS has not before been documented in the literature, this study is distinctive. A realistic example of commerce students’ career selection problem is discussed.